2018
DOI: 10.1038/s41598-018-21180-9
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of heat and charge transport by Majorana fermions

Abstract: We investigate theoretically thermal and electrical conductances for the system consisting of a quantum dot (QD) connected both to a pair of Majorana fermions residing at the edges of a Kitaev wire and two metallic leads. We demonstrate that both quantities reveal pronounced resonances, whose positions can be controlled by tuning of an asymmetry of the couplings of the QD and a pair of MFs. Similar behavior is revealed for the thermopower, Wiedemann-Franz law and dimensionless thermoelectric figure of merit. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…In a structure with a QD coupled to two electrodes, López et al showed that the thermopower will change its sign by changing the direct hybridization between the MBSs, a good evidence of the existence of MBSs [35]. The sign change of the thermopower was also subsequently found in systems of a QD with two [36] or three [37] electrodes. Moreover, it was demonstrated that the relationship between the shot noise and thermoelectric quantities may provide a purely electrical way to detect the charge-neutral MBSs [38,39].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a structure with a QD coupled to two electrodes, López et al showed that the thermopower will change its sign by changing the direct hybridization between the MBSs, a good evidence of the existence of MBSs [35]. The sign change of the thermopower was also subsequently found in systems of a QD with two [36] or three [37] electrodes. Moreover, it was demonstrated that the relationship between the shot noise and thermoelectric quantities may provide a purely electrical way to detect the charge-neutral MBSs [38,39].…”
Section: Introductionmentioning
confidence: 96%
“…1) to study the properties of the thermopower. In the nanosystem we considered, the strong Coulomb interaction in the dot, which has been neglected in previous works [18,[22][23][24][34][35][36][37][38][39], is taken into account. Furthermore, we consider that only one spin component of the QD spin is coupled to the MBSs due to the chiral nature of the MBSs [40].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, we believe that the correspondence presented in this work could still hold for certain cases, as in the conventional Kondo effect. [ 50–55 ] However, the correspondence will non‐necessarily hold under two‐stage Kondo effect due to that Fano interference seems to be fragile in the presence of induced superconducting pairing correlations. [ 56 ] In any of these two cases, more research should be carried out in order to confirm our thoughts, which is a matter of further studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10–15 ] Nevertheless, distinguishing between MBSs and other spurious‐zero energy modes is challenging, since the ZBCP can also be caused by disorder, multi‐band effects, weak antilocalization, the Kondo effect, and Andreev bound states (ABSs). [ 16 ] Currently, distinguishing MBSs from ABSs is one of the most critical challenges, which has led recently to considerable experimental and theoretical efforts, [ 16–26 ] mostly focused on quantum dots coupled to topological superconductors (QD–MBSs configurations). Indeed, evidence of their existence have been shown by probing their transport conductance spectrum, [ 21,27,28 ] thermal conductance, [ 29 ] current noise, [ 28,30,31 ] ac Josephson effect, [ 32,33 ] and particularly, Fano resonances [ 9,34–40 ]…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the term cos(l √ b) in ε M is responsible for the oscillatory pattern in conductance as function of the magnetic field. The couplings between the upper/lower MBSs and the QD are given by λ 1 and λ 2 , respectively 34 . As known, the Hamiltonian of Eq.…”
Section: The Modelmentioning
confidence: 99%